Methods for monitoring mechanical loads in metal products - Oliinyk, Vasyl (National Technical University "Kharkiv Polytechnic Institute", 2025)
This abstract outlines key methods for monitoring mechanical loads in metal products, highlighting their principles, advantages, and applications. Special attention is paid to electromagnetic methods, noted for their speed and non-contact nature. The study emphasizes the importance of precise, real-time load monitoring in industrial applications.
Keywords: mechanical load; monitoring methods; metal products; electromagnetic method; non-destructive testing